A kind of functional decorative black film and preparation method thereof
By combining modified silica and core-shell structure polyacrylate, the near-infrared light transmittance and alkali resistance of PET films are improved, and the shortcomings of existing films in terms of invisibility and alkali resistance are solved, and the implementation of the realization of the films is achieved. The effect of low transmittance in visible light and high transmittance in near infrared light.
Patent Information
- Application Number
- CN202410062095.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-16
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-01-16
AI Technical Summary
The existing PET films have shortcomings in near-infrared light transmittance and alkali resistance, which are difficult to meet the needs of modern technology, especially the need to realize stealth functions in automotive radars, electronic products and military products.
Using polyacrylates with modified silica and core-shell structures, the titanium-doped mesoporous silica nanomaterials and MXene quantum dots are synthesized by hydrothermal, combined with hydroxyl condensation reaction to improve the near-infrared light transmittance of the film and Alkaline resistance and PET films were prepared by extrusion.
It realizes the film with low transmittance in visible light, high transmittance in near infrared light, and has excellent alkali resistance and toughness. It is suitable for stealth applications of military products, automotive radars and electronic consumer products.
Smart Images

Figure BDA0004666905000000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thin films, and in particular to a functional decorative black film and a preparation method thereof. Background Art
[0002] PET film is made of polyethylene terephthalate (PET) as the main raw material by extrusion into sheets, and then stretched into film materials. Due to its high rigidity, hardness, excellent mechanical and chemical properties and dimensional stability, it can be widely used in food and pharmaceutical chemical packaging, decoration, electronics, electrical insulation, screen protection and other fields. With the advancement of science and technology, people have new demands for the functions of PET film, for example, films with high transmittance to near-infrared light and low transmittance to visible light. Such films can be used in automotive radars, electronic products, security products, and military products to achieve near-infrared stealth functions. In addition, due to different use environments, it may be necessary to improve the alkali resistance and toughness of PET film to ensure that it still has excellent performance under alkaline conditions.
[0003] Therefore, researchers need to provide a PET film with low visible light transmittance, high near-infrared light transmittance, alkali resistance and excellent toughness. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a functional decorative black film and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A functional decorative black film, comprising a back glue layer and a substrate layer; the back glue layer is an epoxy resin adhesive coated on one side of the substrate layer; the substrate layer comprises the following raw materials in parts by weight: 100 parts of PET resin, 2-3 parts of antioxidant, 0.5-2 parts of heat stabilizer, 5-8 parts of modified polyacrylate, 0.1-1 parts of lubricant, 15-20 parts of modified silicon dioxide, 2-4 parts of curing agent, and 3-5 parts of black toner;
[0007] The modified silicon dioxide is prepared by the following steps:
[0008] Step A1, anhydrous ethanol, ammonia water and deionized water are mixed and stirred for 5 minutes under sealed conditions, dodecyl ammonium bromide is added and stirred continuously for 20 minutes, and ultrasonicated at room temperature for 15 minutes, and then during the stirring process, the mixed solution A is slowly added with a constant pressure separatory funnel, and the dropping time is controlled to be 20-40 minutes. After the dropwise addition is completed, stirring is continued for 4-6 hours. After the reaction is completed, the precipitate is filtered and washed to a neutral pH, and the precipitate is vacuum dried at 80°C for 12 hours, and then transferred to a muffle furnace, and calcined at 550°C for 3-5 hours to obtain Ge-SiO2 nanomaterials;
[0009] In step A1, titanium-doped mesoporous silica nanomaterials are hydrothermally synthesized using tetraethyl orthosilicate as a silicon source and organic germanium as a germanium source, and then calcined at high temperature to further increase the specific surface area of the nanomaterial. Mesoporous silica has a unique pore structure and can provide abundant growth sites for vanadium dioxide in subsequent experiments. Silica itself has excellent optical properties and excellent transmittance to the propagation of light. It hardly absorbs visible light and infrared light, and has excellent heat resistance and chemical stability, and can still maintain good optical properties in a high temperature environment. The doping of germanium further improves the near-infrared light transmittance of the nanomaterial, because germanium has excellent near-infrared light transmittance and a low infrared light absorption coefficient, and the addition of germanium also improves the corrosion resistance of the matrix.
[0010] Furthermore, the dosage ratio of anhydrous ethanol, ammonia water, deionized water, dodecyl ammonium bromide and mixed solution A is 100 mL: 9 mL: 38 mL: 0.8-2.4 g: 28-30.5 mL, and the mixed solution A is prepared by stirring and mixing ethyl orthosilicate, organic germanium and anhydrous ethanol in a dosage ratio of 3-5.5 mL: 0.02-0.1 g: 25 mL.
[0011] Step A2, add 5 mg / mL titanium carbide monolayer dispersion and Ge-SiO2 nanomaterial to 0.5 mol / L sodium hydroxide ethanol solution and mix evenly, and transfer it to a polytetrafluoroethylene reactor to react at 100°C for 3 hours. After the reaction is completed, cool it to room temperature, ultrasonicate the mixture in a water bath for 2 hours, centrifuge it at 500 rpm for 30 minutes, take out the upper suspension and freeze-dry it for 24 hours, then place the dried powder in a muffle furnace and calcine it at 600°C for 20 minutes under air conditions, wash, centrifuge, and dry it at 50°C for 6 hours to obtain MXene QDs@Ge-SiO2 nanomaterial;
[0012] In step A2, the excellent pore structure of Ge-SiO2 nanomaterials is utilized. MXene QDs are first synthesized in the voids of Ge-SiO2 nanomaterials by a solvothermal reaction, and then the pores are collapsed to form a dense shell layer through high-temperature calcination, thereby achieving the encapsulation of quantum dots and improving the stability of quantum dots. In addition, MXene quantum dots significantly reduce the visible light transmittance of the matrix. This is because quantum dots have a special band structure and surface plasmon resonance effect, which makes them have a strong absorption effect in the visible light region.
[0013] Furthermore, the usage ratio of titanium carbide monolayer dispersion, Ge-SiO2 nanomaterial and sodium hydroxide ethanol solution is 2-4mL:0.5-1.5g:30mL.
[0014] Step A3, dispersing KH-560 and MXene QDs@Ge-SiO2 nanomaterials in a mixture of deionized water and anhydrous ethanol, raising the system temperature to 90°C, stirring and reacting for 5-7 hours, and after the reaction is completed, cooling to room temperature, centrifuging, washing with anhydrous ethanol, and drying at 80°C for 2 hours to obtain modified silica;
[0015] In step A3, KH-560 is grafted onto the surface of MXene QDs@Ge-SiO2 nanomaterials by hydroxyl condensation reaction, which improves the dispersibility of the nanomaterials and further improves the optical properties of the modified silica in the matrix; in addition, the free epoxy groups on the surface of the nanomaterials can also react with a small amount of active groups in the PET resin, so that the nanomaterials are well fixed in the matrix, avoiding the loss of nanomaterials during the production process.
[0016] Furthermore, the dosage ratio of KH-560, MXene QDs@Ge-SiO2 nanomaterial, deionized water and anhydrous ethanol is 2-3mL:0.5-2g:5mL:45mL.
[0017] The modified polyacrylate is prepared by the following steps:
[0018] Step B1, adding deionized water, sodium dodecyl sulfate, potassium carbonate, butyl acrylate, ethyl acrylate and allyl methacrylate into a reactor, then passing N2 into the reaction system for 20 min, then adding potassium persulfate into the system, continuing to stir and react for 2-3 h, and after the reaction is completed, obtaining a seed emulsion;
[0019] Furthermore, the usage ratio of deionized water, sodium dodecyl sulfate, potassium carbonate, butyl acrylate, ethyl acrylate, allyl methacrylate and potassium persulfate is 60g: 0.25-0.5g: 0.2-0.4g: 20-40g: 5-10g: 2-3g: 0.08-0.16g.
[0020] Step B2, adding deionized water, potassium persulfate and seed emulsion into a reactor, stirring for 15-25 minutes under nitrogen, then slowly dripping methyl methacrylate, methacryloyloxymethyltrimethoxysilane and methacrylate phosphate into the reaction system, raising the system temperature to 75°C after dripping, continuing the reaction for 30 minutes, and after the reaction is completed, lowering the temperature to 65°C, adding 0.25wt% magnesium sulfate solution to demulsify, washing, filtering and drying to obtain modified polyacrylate;
[0021] In step B2, a shell structure is grafted on the surface of the seed emulsion by a semi-continuous emulsion polymerization method to synthesize a polyacrylate with a core-shell structure, thereby improving the toughness of the substrate. This is because after the substrate is subjected to external force, the modified polyacrylate can serve as a stress concentration center to generate cracks or shear bands in the substrate, and the cracks or shear bands absorb a large amount of energy during their occurrence and growth, thereby improving the toughness of the substrate. The methacrylic acid phosphate contained in the shell layer can improve the alkali resistance of the substrate, because the phosphate group has a special molecular structure and excellent alkali resistance. The methacryloyloxymethyltrimethoxysilane contained in the shell layer can improve the water resistance of the substrate, because siloxane can hydrolyze the silanol bonds, and the silanol bonds can undergo condensation reactions with the hydroxyl groups on the surface of the modified silica and the free hydroxyl groups in the PET resin to form a cross-linked structure.
[0022] Furthermore, the usage ratio of deionized water, potassium persulfate, seed emulsion, methyl methacrylate, methacryloyloxymethyltrimethoxysilane, methacrylate phosphate and magnesium sulfate solution is 25-75g: 0.05-0.15g: 30-90g: 5-9g: 1g: 1g: 200mL.
[0023] A method for preparing a functional decorative black film comprises the following steps:
[0024] Step S1, weighing raw materials according to weight, adding the raw materials into a granulator for mixing and granulation to obtain PET polyester particles, the mixing temperature is 120-140° C.;
[0025] Step S2, the PET polyester particles are passed through a fully automatic vacuum drum, an extruder, and a biaxial stretching unit to produce a PET film, so as to obtain a substrate layer, and the film outlet temperature is controlled to be 90-100° C.;
[0026] Step S3: After cooling, evenly coat the adhesive on one side of the PET film, and dry it at 60-80° C. for 2-3 minutes to form a back adhesive layer, thereby obtaining a functional decorative black film.
[0027] Beneficial effects of the present invention:
[0028] The functional decorative black film provided by the present invention firstly modifies silicon dioxide and uses it as an inorganic filler to make the film have a lower transmittance under visible light and a higher transmittance under near-infrared light; secondly, polyacrylate with a core-shell structure is synthesized to improve the alkali resistance and water resistance of the film. Therefore, the black film provided by the present invention can be applied to military products, automotive radars, security, electronic consumer products, robots and drones to achieve invisibility under near-infrared light.
[0029] In the modified silica, first, titanium-doped mesoporous silica nanomaterials are hydrothermally synthesized using tetraethyl orthosilicate as a silicon source and organic germanium as a germanium source, and then calcined at high temperature to further increase the specific surface area of the nanomaterial. Mesoporous silica has a unique pore structure, which can provide abundant growth sites for vanadium dioxide in subsequent experiments. Silica itself has excellent optical properties and excellent transmittance to the propagation of light. It absorbs almost no visible and infrared light, and has excellent heat resistance and chemical stability, and can still maintain good optical properties in a high temperature environment. The doping of germanium further improves the near-infrared light transmittance of the nanomaterial, because germanium has excellent near-infrared light transmittance and a low infrared light absorption coefficient, and the addition of germanium also improves the corrosion resistance of the matrix. Secondly, by utilizing the excellent pore structure of Ge-SiO2 nanomaterials, MXene QDs were first synthesized in the voids of Ge-SiO2 nanomaterials by solvent thermal reaction, and then calcined at high temperature to collapse the pores to form a dense shell layer, thereby achieving the encapsulation of quantum dots and improving the stability of quantum dots; in addition, MXene quantum dots significantly reduced the visible light transmittance of the matrix, which is due to the special band structure and surface plasmon resonance effect of quantum dots, which makes them have strong absorption in the visible light region. Finally, KH-560 was grafted on the surface of MXene QDs@Ge-SiO2 nanomaterials by hydroxyl condensation reaction, which improved the dispersibility of nanomaterials and further improved the optical properties of modified silica in the matrix; in addition, the free epoxy groups on the surface of nanomaterials can also react with a small amount of active groups in PET resin, so that the nanomaterials are well fixed in the matrix, avoiding the loss of nanomaterials during the production process.
[0030] In the modified polyacrylate, a shell structure is grafted on the surface of the seed emulsion by a semi-continuous emulsion polymerization method to synthesize a polyacrylate with a core-shell structure, thereby improving the toughness of the matrix. This is because after the matrix is subjected to external force, the modified polyacrylate can serve as a stress concentration center to generate cracks or shear bands in the matrix, and the cracks or shear bands absorb a large amount of energy during their occurrence and growth, thereby improving the toughness of the matrix. The methacrylic phosphate contained in the shell layer can improve the alkali resistance of the matrix, because the phosphate group has a special molecular structure and excellent alkali resistance. The methacryloyloxymethyltrimethoxysilane contained in the shell layer can improve the water resistance of the matrix, because siloxane can hydrolyze the silanol bonds, and the silanol bonds can undergo condensation reactions with the hydroxyl groups on the surface of the modified silica and the free hydroxyl groups in the PET resin to form a cross-linked structure. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] 1) Modified silica is prepared by the following steps:
[0034] Step A1, 100mL of anhydrous ethanol, 9mL of ammonia water and 38mL of deionized water were mixed and stirred under sealed conditions for 5min, 0.8mL of dodecyl ammonium bromide was added and stirred continuously for 20min, and ultrasonicated at room temperature for 15min, and then 28mL of mixed solution A was slowly added with a constant pressure separatory funnel during the stirring process, and the dropping time was controlled to 20min. After the dropwise addition was completed, stirring was continued for 4h. After the reaction was completed, the precipitate was filtered and washed until the pH was neutral. After the precipitate was vacuum dried at 80°C for 12h, it was transferred to a muffle furnace and calcined at 550°C for 3h to obtain Ge-SiO2 nanomaterials. The mixed solution A was prepared by stirring and mixing ethyl orthosilicate, organic germanium and anhydrous ethanol in a dosage ratio of 3mL:0.02g:25mL;
[0035] Step A2, add 2mL, 5mg / mL titanium carbide monolayer dispersion and 0.5g Ge-SiO2 nanomaterial to 30mL 0.5mol / L sodium hydroxide ethanol solution and mix evenly, and transfer it to a polytetrafluoroethylene reactor and react at 100°C for 3h. After the reaction is completed, cool it to room temperature, ultrasonicate the mixture in a water bath for 2h, centrifuge it at 500rpm for 30min, take out the upper suspension and freeze-dry it for 24h, then place the dried powder in a muffle furnace and calcine it at 600°C for 20min under air conditions, wash, centrifuge, and dry it at 50°C for 6h to obtain MXene QDs@Ge-SiO2 nanomaterial;
[0036] Step A3, disperse 2 mL of KH-560 and 0.5 g of MXene QDs@Ge-SiO2 nanomaterials in a mixture of 5 mL of deionized water and 45 mL of anhydrous ethanol, raise the system temperature to 90 ° C, continue stirring and react for 5 hours, after the reaction is completed, cool to room temperature, centrifuge, wash with anhydrous ethanol, and dry at 80 ° C for 2 hours to obtain modified silica.
[0037] 2) The modified polyacrylate is prepared by the following steps:
[0038] Step B1, 60g of deionized water, 0.25g of sodium dodecyl sulfate, 0.2g of potassium carbonate, 20g of butyl acrylate, 5g of ethyl acrylate and 2g of allyl methacrylate were added into a reactor, and then N2 was introduced into the reaction system for 20min, and then 0.08g of potassium persulfate was added into the system, and the reaction was continued with stirring for 2h. After the reaction was completed, a seed emulsion was obtained;
[0039] Step B2, add 25g of deionized water, 0.05g of potassium persulfate and 30g of seed emulsion into the reactor, stir for 15min under nitrogen, then slowly drip 5g of methyl methacrylate, 1g of methacryloyloxymethyltrimethoxysilane and 1g of methacrylic acid phosphate into the reaction system, after dripping, raise the system temperature to 75°C, continue to react for 30min, after the reaction is completed, lower the temperature to 65°C, add 200mL, 0.25wt% magnesium sulfate solution to demulsify, wash, filter and dry to obtain modified polyacrylate.
[0040] Example 2
[0041] 1) Modified silica is prepared by the following steps:
[0042] Step A1, 100mL of anhydrous ethanol, 9mL of ammonia water and 38mL of deionized water were mixed and stirred under sealed conditions for 5min, 1.6mL of dodecyl ammonium bromide was added and stirred continuously for 20min, and ultrasonicated at room temperature for 15min, and then 29mL of mixed solution A was slowly added with a constant pressure separatory funnel during the stirring process, and the dropping time was controlled to 30min. After the dropwise addition was completed, stirring was continued for 5h. After the reaction was completed, the precipitate was filtered and washed to a neutral pH. After the precipitate was vacuum dried at 80°C for 12h, it was transferred to a muffle furnace and calcined at 550°C for 4h to obtain Ge-SiO2 nanomaterials. The mixed solution A was prepared by stirring and mixing ethyl orthosilicate, organic germanium and anhydrous ethanol in a dosage ratio of 4mL:0.05g:25mL;
[0043] Step A2, add 3mL, 5mg / mL titanium carbide monolayer dispersion and 1g Ge-SiO2 nanomaterial to 30mL 0.5mol / L sodium hydroxide ethanol solution and mix evenly, and transfer it to a polytetrafluoroethylene reactor and react at 100°C for 3h. After the reaction is completed, cool it to room temperature, ultrasonicate the mixture in a water bath for 2h, centrifuge it at 500rpm for 30min, take out the upper suspension and freeze-dry it for 24h, then place the dried powder in a muffle furnace and calcine it at 600°C for 20min under air conditions, wash, centrifuge, and dry it at 50°C for 6h to obtain MXene QDs@Ge-SiO2 nanomaterial;
[0044] Step A3, disperse 2.5mL KH-560 and 1g MXene QDs@Ge-SiO2 nanomaterials in a mixture of 5mL deionized water and 45mL anhydrous ethanol, raise the system temperature to 90°C, continue stirring and react for 6h, after the reaction is completed, cool to room temperature, centrifuge, wash with anhydrous ethanol, and dry at 80°C for 2h to obtain modified silica.
[0045] 2) The modified polyacrylate is prepared by the following steps:
[0046] Step B1, 60g of deionized water, 0.35g of sodium dodecyl sulfate, 0.3g of potassium carbonate, 30g of butyl acrylate, 7g of ethyl acrylate and 2.5g of allyl methacrylate were added into a reactor, and then N2 was introduced into the reaction system for 20min, and then 0.12g of potassium persulfate was added into the system, and the reaction was continued with stirring for 2.5h. After the reaction was completed, a seed emulsion was obtained;
[0047] Step B2, add 50g of deionized water, 0.1g of potassium persulfate and 60g of seed emulsion into the reactor, stir for 20min under nitrogen, then slowly drip 7g of methyl methacrylate, 1g of methacryloyloxymethyltrimethoxysilane and 1g of methacrylate phosphate into the reaction system, after dripping, raise the system temperature to 75°C, continue to react for 30min, after the reaction is completed, lower the temperature to 65°C, add 200mL, 0.25wt% magnesium sulfate solution to demulsify, wash, filter and dry to obtain modified polyacrylate.
[0048] Example 3
[0049] 1) Modified silica is prepared by the following steps:
[0050] Step A1, 100mL of anhydrous ethanol, 9mL of ammonia water and 38mL of deionized water were mixed and stirred under sealed conditions for 5min, 2.4mL of dodecyl ammonium bromide was added and stirred continuously for 20min, and ultrasonicated at room temperature for 15min, and then 30.5mL of mixed solution A was slowly added with a constant pressure separatory funnel during the stirring process, and the dropping time was controlled to 40min. After the dropwise addition was completed, stirring was continued for 6h. After the reaction was completed, the precipitate was filtered and washed to a neutral pH. After the precipitate was vacuum dried at 80°C for 12h, it was transferred to a muffle furnace and calcined at 550°C for 5h to obtain Ge-SiO2 nanomaterials. The mixed solution A was prepared by stirring and mixing ethyl orthosilicate, organic germanium and anhydrous ethanol in a dosage ratio of 5.5mL:0.1g:25mL;
[0051] Step A2, add 4mL, 5mg / mL titanium carbide monolayer dispersion and 1.5g Ge-SiO2 nanomaterial to 30mL 0.5mol / L sodium hydroxide ethanol solution and mix evenly, and transfer it to a polytetrafluoroethylene reactor and react at 100°C for 3h. After the reaction is completed, reduce the temperature to room temperature, ultrasonicate the mixture in a water bath for 2h, centrifuge it at 500rpm for 30min, take out the upper suspension and freeze-dry it for 24h, then place the dried powder in a muffle furnace and calcine it at 600°C for 20min under air conditions, wash, centrifuge, and dry it at 50°C for 6h to obtain MXene QDs@Ge-SiO2 nanomaterial;
[0052] Step A3, disperse 3 mL of KH-560 and 2 g of MXene QDs@Ge-SiO2 nanomaterials in a mixture of 5 mL of deionized water and 45 mL of anhydrous ethanol, raise the system temperature to 90 ° C, and continue stirring to react for 7 hours. After the reaction is completed, cool to room temperature, centrifuge, wash with anhydrous ethanol, and dry at 80 ° C for 2 hours to obtain modified silica.
[0053] 2) The modified polyacrylate is prepared by the following steps:
[0054] Step B1, 60g of deionized water, 0.5g of sodium dodecyl sulfate, 0.4g of potassium carbonate, 40g of butyl acrylate, 10g of ethyl acrylate and 3g of allyl methacrylate were added into a reactor, and then N2 was introduced into the reaction system for 20min, and then 0.16g of potassium persulfate was added into the system, and the reaction was continued with stirring for 3h. After the reaction was completed, a seed emulsion was obtained;
[0055] Step B2, add 75g of deionized water, 0.15g of potassium persulfate and 90g of seed emulsion into the reactor, stir for 25min under nitrogen, then slowly drip 9g of methyl methacrylate, 1g of methacryloyloxymethyltrimethoxysilane and 1g of methacrylic acid phosphate into the reaction system, after dripping, raise the system temperature to 75°C, continue to react for 30min, after the reaction is completed, lower the temperature to 65°C, add 200mL, 0.25wt% magnesium sulfate solution to demulsify, wash, filter and dry to obtain modified polyacrylate.
[0056] Example 4
[0057] A functional decorative black film comprises a back glue layer and a substrate layer; the back glue layer is an epoxy resin adhesive coated on one side of the substrate layer; the substrate layer comprises the following raw materials in parts by weight: 100 parts of PET resin, 2 parts of antioxidant B225, 0.5 parts of thermal stabilizer FT-4288, 5 parts of modified polyacrylate prepared in Example 1, 0.1 parts of polyethylene wax, 15 parts of modified silicon dioxide prepared in Example 1, 2 parts of diaminodiphenyl sulfone, and 3 parts of masonry black; the preparation method comprises the following steps:
[0058] Step S1, weighing raw materials according to weight, adding the raw materials into a granulator for mixing and granulation to obtain PET polyester particles, the mixing temperature is 120° C.;
[0059] Step S2, the PET polyester particles are passed through a fully automatic vacuum drum, an extruder, and a biaxial stretching unit to produce a PET film, so as to obtain a substrate layer, and the film outlet temperature is controlled to be 90° C.;
[0060] Step S3: After cooling, evenly coat the adhesive on one side of the PET film and dry it at 60° C. for 2 minutes to form a back adhesive layer, thereby obtaining a functional decorative black film.
[0061] Example 5
[0062] A functional decorative black film comprises a backing layer and a substrate layer; the backing layer is an epoxy resin adhesive coated on one side of the substrate layer; the substrate layer comprises the following raw materials in parts by weight: 100 parts of PET resin, 2.5 parts of antioxidant B225, 1 part of thermal stabilizer FT-4288, 6 parts of modified polyacrylate prepared in Example 2, 0.5 parts of polyethylene wax, 17 parts of modified silicon dioxide prepared in Example 2, 3 parts of diaminodiphenyl sulfone, and 4 parts of masonry black; the preparation method comprises the following steps:
[0063] Step S1, weighing raw materials according to weight, adding the raw materials into a granulator for mixing and granulation to obtain PET polyester particles, the mixing temperature is 130° C.;
[0064] Step S2, the PET polyester particles are passed through a fully automatic vacuum drum, an extruder, and a biaxial stretching unit to produce a PET film, so as to obtain a substrate layer, and the film outlet temperature is controlled to be 95° C.;
[0065] Step S3: After cooling, evenly coat the adhesive on one side of the PET film and dry it at 70° C. for 2 minutes to form a back adhesive layer, thereby obtaining a functional decorative black film.
[0066] Example 6
[0067] A functional decorative black film comprises a back glue layer and a substrate layer; the back glue layer is an epoxy resin adhesive coated on one side of the substrate layer; the substrate layer comprises the following raw materials in parts by weight: 100 parts of PET resin, 3 parts of antioxidant B225, 2 parts of thermal stabilizer FT-4288, 8 parts of modified polyacrylate prepared in Example 3, 1 part of polyethylene wax, 20 parts of modified silicon dioxide prepared in Example 3, 4 parts of diaminodiphenyl sulfone, and 5 parts of masonry black; the preparation method comprises the following steps:
[0068] Step S1, weighing raw materials according to weight, adding the raw materials into a granulator for mixing and granulation to obtain PET polyester particles, the mixing temperature is 140° C.;
[0069] Step S2, the PET polyester particles are passed through a fully automatic vacuum drum, an extruder, and a biaxial stretching unit to produce a PET film, thereby obtaining a substrate layer, and the film outlet temperature is controlled to be 100° C.;
[0070] Step S3: After cooling, evenly coat the adhesive on one side of the PET film and dry it at 80° C. for 3 minutes to form a back adhesive layer, thereby obtaining a functional decorative black film.
[0071] Comparative Example 1
[0072] This comparative example is a PET polyester film, which differs from Example 6 in that an equal amount of silicon dioxide is used to replace the modified silicon dioxide prepared in Example 3, and the rest are the same.
[0073] Comparative Example 2
[0074] This comparative example is a PET polyester film, which differs from Example 6 in that an equal amount of polyamide resin is used to replace the modified polyacrylate prepared in Example 3, and the rest are the same.
[0075] The films prepared in Examples 4-6 and Comparative Examples 1-2 were applied to the glass surface to obtain samples for performance testing: Transmittance test: Detected by UV-Vis-Infrared spectrometer (UV-6300 and UV-3600); Alkali resistance: After the sample was immersed in 0.5 mol / L sodium hydroxide solution for 72 hours, the film on the surface of the sample was observed to see if it was deformed; Tensile strength test: The tensile strength test was performed according to GB / T13022-1991 standard. The test results are shown in Table 1:
[0076] Table 1
[0077]
[0078] As can be seen from Table 1, the film prepared by the present invention has a lower visible light transmittance (1.0-2.6%), a higher near-infrared light transmittance (98.2-98.9%), and has excellent alkali resistance and toughness.
[0079] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A functional decorative black film, characterized in that: It comprises a back adhesive layer and a substrate layer; the back adhesive layer is an epoxy resin adhesive coated on one side of the substrate layer; the substrate layer comprises the following raw materials in parts by weight: 100 parts of PET resin, 2-3 parts of antioxidant, 0.5-2 parts of heat stabilizer, 5-8 parts of modified polyacrylate, 0.1-1 parts of lubricant, 15-20 parts of modified silicon dioxide, 2-4 parts of curing agent, and 3-5 parts of black toner; The modified silicon dioxide is prepared by the following steps: Step A1, anhydrous ethanol, ammonia water and deionized water are mixed and stirred for 5 minutes under sealed conditions, dodecyl ammonium bromide is added and stirred continuously for 20 minutes, and ultrasonicated at room temperature for 15 minutes, and then, during the stirring process, mixed solution A is slowly added with a constant pressure separatory funnel, and the dropwise addition time is controlled to be 20-40 minutes. After the dropwise addition is completed, stirring is continued for 4-6 hours. After the reaction is completed, the precipitate is filtered and washed until the pH is neutral. After the precipitate is vacuum dried at 80° C. for 12 hours, it is transferred to a muffle furnace and calcined at 550° C. for 3-5 hours to obtain Ge-SiO2 nanomaterials. The amount ratio of anhydrous ethanol, ammonia water, deionized water, dodecyl ammonium bromide and mixed solution A is 100 mL: 9 mL: 38 mL: 0.8-2.4 g: 28-30.5 mL, and the mixed solution A is prepared by stirring and mixing ethyl orthosilicate, organic germanium and anhydrous ethanol in an amount ratio of 3-5.5 mL: 0.02-0.1 g: 25 mL; Step A2, add 5 mg / mL titanium carbide monolayer dispersion and Ge-SiO2 nanomaterial to 0.5 mol / L sodium hydroxide ethanol solution and mix evenly, and transfer it to a polytetrafluoroethylene reactor to react at 100°C for 3 hours. After the reaction is completed, reduce the temperature to room temperature, ultrasonicate the mixture in a water bath for 2 hours, centrifuge it at 500 rpm for 30 minutes, take out the upper suspension and freeze-dry it for 24 hours, then place the dried powder in a muffle furnace and calcine it at 600°C for 20 minutes under air conditions, wash, centrifuge, and dry it at 50°C for 6 hours to obtain MXene QDs@Ge-SiO2 nanomaterial; Step A3, dispersing KH-560 and MXene QDs@Ge-SiO2 nanomaterials in a mixture of deionized water and anhydrous ethanol, raising the system temperature to 90°C, stirring and reacting for 5-7 hours, and after the reaction is completed, cooling to room temperature, centrifuging, washing with anhydrous ethanol, and drying at 80°C for 2 hours to obtain modified silica; The modified polyacrylate is prepared by the following steps: Step B1, adding deionized water, sodium dodecyl sulfate, potassium carbonate, butyl acrylate, ethyl acrylate and allyl methacrylate into a reactor, then introducing N2 into the reaction system for 20 min, then adding potassium persulfate into the system, continuing to stir and react for 2-3 h, and after the reaction is completed, obtaining a seed emulsion; Step B2, add deionized water, potassium persulfate and seed emulsion into the reactor, stir for 15-25 minutes under nitrogen, then slowly drip methyl methacrylate, methacryloyloxymethyltrimethoxysilane and methacrylate phosphate into the reaction system, after dripping, raise the system temperature to 75°C, continue to react for 30 minutes, after the reaction is completed, lower the temperature to 65°C, add 0.25wt% magnesium sulfate solution to demulsify, wash, filter and dry to obtain modified polyacrylate.
2. The functional decorative black film according to claim 1, characterized in that: In step A2, the usage ratio of titanium carbide monolayer dispersion, Ge-SiO2 nanomaterial and sodium hydroxide ethanol solution is 2-4 mL: 0.5-1.5 g: 30 mL.
3. The functional decorative black film according to claim 1, characterized in that: In step A3, the dosage ratio of KH-560, MXeneQDs@Ge-SiO2 nanomaterial, deionized water and anhydrous ethanol is 2-3mL:0.5-2g:5mL:45mL.
4. The functional decorative black film according to claim 1, characterized in that: In step B1, the usage ratio of deionized water, sodium dodecyl sulfate, potassium carbonate, butyl acrylate, ethyl acrylate, allyl methacrylate and potassium persulfate is 60g: 0.25-0.5g: 0.2-0.4g: 20-40g: 5-10g: 2-3g: 0.08-0.16g.
5. The functional decorative black film according to claim 1, characterized in that: In step B2, the dosage ratio of deionized water, potassium persulfate, seed emulsion, methyl methacrylate, methacryloyloxymethyltrimethoxysilane, methacrylate phosphate and magnesium sulfate solution is 25-75 g: 0.05-0.15 g: 30-90 g: 5-9 g: 1 g: 1 g: 200 mL.
6. The method for preparing a functional decorative black film according to claim 1, characterized in that: The following steps are involved: Step S1, weighing raw materials according to weight, adding the raw materials into a granulator for mixing and granulation to obtain PET polyester particles, the mixing temperature is 120-140° C.; Step S2, the PET polyester particles are passed through a fully automatic vacuum drum, an extruder, and a biaxial stretching unit to produce a PET film, so as to obtain a substrate layer, and the film outlet temperature is controlled to be 90-100° C.; Step S3: After cooling, evenly coat the adhesive on one side of the PET film, and dry it at 60-80° C. for 2-3 minutes to form a back adhesive layer, thereby obtaining a functional decorative black film.
